Critical Discourse Analysis of Theo Van Leeuwen Inclusion Video Podcast on the Gritte Agatha Youtube Channel - Wulandari, Putri Ayu; Zamzani; Liliani, Else (International Journal of Education and Teaching Zone, 2023)
Podcasts as a form of Youtube content are considered to have good popularity because provide the information the user needs. One of the current Youtube channel loved by social media users is Gritte Agatha's channel. In one video which raised the theme of bullying. This study aims to analyze Theo Van's inclusion theory Leewen in one of the video podcasts on the Gritte Agatha YouTube channel. This research using descriptive qualitative method. Data collection is done by using analysis document. The results of the study show that the total is present 15 data included in the theory inclusion strategy from Theo Van Leeuwen with 5 inclusion strategies, namely objectivity-abstract. So it can be concluded that in the video podcast from Gritte Agatha's YouTube channel entitled "Severe Trauma Due To Being Bully*Y, Until Entering A Mental Hospital ", both the presenter and resource person at the event told stories without marginalizing the actors.